ANALISIS PROGRAM BIMBINGAN PERKAWINAN DALAM MEWUJUDKAN KELUARGA SAKINAH STUDI KASUS DI KUA LOWOKWARU KOTA MALANG - Maulidiyah Wati; Ahmad Subekti; Ibnu Jazari (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2019)
In marriage, of course, all of them have desires in their marriage with the creation of a family of sakinah, mawaddah, warahmah. In the context of realizing a marriage that is sakinah, mawaddah, wa rahmah, the ministry of religion in the Director General Guidance of Islamic Community Guidance number 379 of 2018 concerning the implementation guidelines for premarital marriage guidance for brides and grooms, it is recommended that every KUA give guidance to prospective bride and groom with basic knowledge about marriage . To achieve the objectives stated above this research was conducted with a type of qualitative research. With the procedure carried out using the method of observation, interviews, and documentation. In this study to reach the sakinah family arranged in the Marriage Guidance Program which is to prepare the family sakinah, build relationships in the family, meet family needs, maintain reproductive health, prepare a quality generation. In the implementation there are also several things that can hamper the smooth running of the program, namely in terms of infrastructure, participants in marriage guidance, funding, summons or promulgation of marital guidance participants. This shows that there are still things that have not been done so well even though they have been well implemented. Kata Kunci: Program Bimbingan Perkawinan, Keluarga, Keluarga Sakinah